Механизм зародышеобразования и расчет полной энергии наноструктур в материальной системе CdTe-ZnTe-HgTe - Симонян, А. К.; Гамбарян, К. М.; Арутюнян, В. М.; Гамбарян, М. К.; Аветисян, Г. А. (Հայաստանի ԳԱԱ)
The continuum elasticity model is applied to quantitatively investigate the growth features and nucleation mechanism of quantum dots, nanopits, and joint QDs-nanopits structures in CdZnHgTe quasyternary material system.
Keywords: Quantum Physics